Potensi Likuifaksi Pada Proyek Pengembangan Infrastruktur Jalan Di Bandara Kualanamu Berdasarkan SNI 1726 : 2019 - Hutagaol, Samuel Parlindungan; Wulandari, Tika Ermita (Universitas Quality, 2024)
Pakam is an area close to Belawan and is also on the coast of North Sumatra which directly faces the Malacca Strait. Based on the land distribution map, Pakam is an area with silt soil, organic soil, peat soil and sand. The characteristics of these four soils are that they have a very low soil carrying capacity, because they contain a lot of water. However, in this coastal area, a road infrastructure development project was built at Kualanamu Airport, changing water to land to replace the old airport in an area that contains a lot of water. The aim of this research is to find out whether there is potential for liquefaction in the project when an earthquake occurs at magnitudes 6.5 SR, 7.5 SR and 8.0 SR and this makes researchers interested in analyzing whether liquefaction occurs in the project area. The research method used is using primary data from project bore log data, then secondary data using data from SNI 1726: 2019 and the PUskim PU Spektra Design website. The research flow is to take soil data from the project and earthquake data according to SNI 1726: 2019 and use earthquake data from Puskim PU Indonesian Spectra Design, then the liquefaction potential analysis calculation method uses the Young-Idriss method and the Idriss Boulanger method. From the results of the calculation analysis, liquefaction did not occur at a depth of 1.50 – 22.95 m at BH.01 and BH.04 based on SNI 1726: 2019 and also based on the Indonesian Puskim PU Spectra Design even though the soil type was dominantly sand and silt.